EMOTIVE LANGUAGE IN POLITICS (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the strategic use of emotive language in political discourse. Emotive language, which appeals to the emotions rather than logic, is a powerful tool used by politicians to influence public opinion, mobilize support, and frame ideological narratives. Through a critical discourse analysis of political speeches, debates, and campaign materials, this study highlights the linguistic techniques and rhetorical patterns that evoke emotional responses from the audience. Emphasis is placed on how emotional triggers such as fear, hope, anger, and pride are deployed across different political contexts. The findings suggest that emotive language not only shapes voter perception but also plays a critical role in the polarization of public discourse. This paper contributes to a deeper understanding of political communication and its psychological underpinnings. This phenomenon reveals the persuasive power of emotion in shaping political realities. Emotive language appeals to human affect rather than to logic or empirical reasoning. It functions through carefully selected vocabulary, metaphorical constructs, tonal emphasis, and rhetorical figures that are designed to elicit emotions such as hope, fear, pride, anger, or unity.